Chairman of the Zamin Interdistrict Economic Court of Jizzakh Region, Independent Researcher of the Academy of Justice of the Republic of Uzbekistan - Nurmurodovich, Madatov Khabibullo (Journal of Innovation in Education and Social Research, 2026)
Corporate conflict is a variety of contradictions or disagreements that arise between participants in a corporate relationship.